Enzymes in synthetic biology - Scrutton, Nigel S. (Methods in enzymology, 2018)
Volume 608 of the series Methods in Enzymology covers key aspects of enzyme discovery, engineering tools and platforms, and examples of applications in the enzymology of synthetic biology. Detailed methods for laboratory use of enzymes in synthetic biology applicationsInformative case history examples illustrating how enzyme and metabolic engineering are used to generate new productsEmphasises latest developments in laboratory automation for the engineering of biologyCovers many aspects of the design, build, test, learn cycle used in synthetic biology.